Islamic and Scientific Worldview: A Few Important Characteristics - Muhammad Mumtaz Ali; Md Maruf Hasan (Penerbit Hellow Pustaka, 2026)
The very existence of Allah SWT is nothing more than fairytales. This notion may arise in the Muslim minds due to the influence of the scientific worldview in the 21st Century. Unregulated social media contents within Muslim countries are rampant nowadays and there are apostates from Muslim youths who create contents to spread atheism through different online platforms. There are translation works of popular science books by prominent authors that are also available in Muslim Countries. The disenchantment of Islam from Muslim minds is slow and gradual process and it leads to pessimism , Islamophobia, apostacy and blasphemy. This research analyzes the deep-rooted problem with the scientific worldview, and it also uses critical thinking method to respond from the Quranic literature. This research finds that despite the dominancy of the scientific worldview; the Quranic literature has the strength to pave an alternative way to defend Islam. In other words, the Quran has unique ways to defend its propositions. This research suggests that Muslim youths must develop critical thinking approach in light with the Quranic Worldview when encountering the scientific worldview.